Islamic Socio-Religious Reflections on Early Marriage, Family Resilience, and Stunting in Sirampog, Brebes - Widyaningrum, Ratna; Hernawati, Sari; Nofik, Khoirun; Syifaudin, Ma'ruf; Helmi Kayana Juwita, Dinda (MUSLIM HERITAGE, 2025)
Early marriage and child stunting remain persistent issues in Sirampog District, Brebes, a highland horticultural area characterized by long farming hours and limited service access in its upper hamlets. Although national and local initiatives including Presidential Regulation No. 72/2021, Jo Kawin Bocah, KUA premarital guidance, and posyandu services are available, policy messages often remain at the level of general moral advice and are not sufficiently translated into practical 1,000-day nutrition behaviors. This study aims to: (1) identify the social and religious determinants of early marriage; (2) assess how family resilience spiritual, economic, relational, and parenting dimensions—shapes child nutritional status; and (3) estimate the relationship between early marriage and stunting after accounting for parenting practices, parental education, economic conditions, and access to health services, while examining the roles of Islamic institutions (mosques, Qur’an learning centers/TPQ, majelis taklim, and Muslimat NU). Using a qualitative instrumental case-study design, data were collected through in-depth interviews, FGDs, observations of health and religious activities, and document analysis, and examined using Reflexive Thematic Analysis with a Framework Matrix. Findings show that early marriage is driven by religious norms framed as “protection from zina,” social pressure to formalize relationships, gaps in religious literacy, and strategies involving unregistered marriagedispensation registration. Child nutrition is more strongly shaped by family resilience spiritual motivation, food planning, supportive marital relations, and age-appropriate feeding practices. The direct link between early marriage and stunting weakens after key household factors are controlled. Islamic institutions are effective when religious messages are paired with actionable nutrition guidance. These results reinforce the relevance of ḥifẓ al-nasl and ḥifẓ al-nafs in stunting prevention.   Abstrak Pernikahan dini dan stunting masih menjadi persoalan utama di Kecamatan Sirampog, Brebes, wilayah pegunungan dengan pekerjaan tani yang panjang dan akses layanan terbatas, terutama di dusun lereng. Meskipun telah tersedia Perpres 72/2021, program Jo Kawin Bocah, bimbingan perkawinan KUA, serta layanan posyandu, pesan kebijakan tentang pendewasaan usia kawin belum cukup terhubung dengan praktik gizi 1.000 HPK. Penelitian ini bertujuan: (1) mengidentifikasi determinan sosial-keagamaan pernikahan dini; (2) menilai pengaruh ketahanan keluarga (spiritual, ekonomi, relasional, dan pengasuhan) terhadap status gizi anak; dan (3) menganalisis keterkaitan pernikahan dini dan stunting setelah mempertimbangkan pengasuhan, pendidikan orang tua, ekonomi, dan akses kesehatan, serta menilai peran institusi Islam (masjid, TPQ, majelis taklim, Muslimat NU) dalam pencegahan. Studi ini menggunakan pendekatan kualitatif dengan wawancara mendalam, FGD, observasi layanan, dan studi dokumen, dianalisis melalui Reflexive Thematic Analysis dan matriks Framework. Hasil menunjukkan bahwa pernikahan dini dipengaruhi oleh norma religius sebagai “pagar zina”, tekanan sosial, rendahnya literasi keagamaan, dan pola nikah siri–dispensasi–pencatatan. Status gizi anak lebih ditentukan oleh ketahanan keluarga melalui motivasi spiritual, pengaturan makanan anak, relasi suami-istri yang suportif, dan keterampilan pemberian MP-ASI. Hubungan langsung pernikahan dini dengan stunting melemah setelah faktor pengasuhan, pendidikan, ekonomi, dan akses layanan dikendalikan. Institusi Islam terbukti efektif ketika pesan keagamaan dipadukan dengan panduan gizi yang aplikatif. Temuan ini menegaskan bahwa pencegahan pernikahan dini dan stunting merupakan amanah syariah dalam kerangka ḥifẓ al-nasl dan ḥifẓ al-nafs.).